Edukasi Literasi Logistik di SMK : Model PKM Inovatif untuk Peningkatan Kesiapan Kerja Siswa - Irwan Chairudin; Yuliantini; Nofrisel; Yulianti Keke; Euis Saribanon (Pusat Riset dan Inovasi Nasional, 2025)
The high unemployment rate among vocational high school (SMK) graduates, particularly those majoring in logistics, has become a major concern in preparing a workforce that meets the needs of the modern industry. Many SMK graduates still lack a comprehensive understanding of logistics business processes, including the crucial role of supply chain management in company operations. Additionally, the lack of practical experience and technical skills has become a major barrier for these students to compete in the job market. To address this issue, this Community Service (PkM) program was designed to enhance both theoretical knowledge and practical skills of students from SMK Negeri 15 Jakarta in the field of supply chain management. The training was conducted in February 2025 by a team of lecturers and professionals from the Jakarta Institute of Transportation and Logistics. The training applied a contextual, practice-based, and participatory approach to create an active and industry-relevant learning experience. The implementation methods included interactive lectures, group discussions, mini supply chain simulations, visual-based media, and real industry case studies. Students were given opportunities to solve supply chain problems directly and practice making decisions based on available data. The results of the training showed a significant improvement in students' understanding of supply chain concepts and processes—from an initial level of 35% to 82%. Moreover, the program successfully increased students' confidence to enter the logistics job market and fostered essential soft skills such as teamwork, communication, and data analysis. As a follow-up initiative, a digital community called the “SMK Logistics Hub” was established as a collaborative platform to support the sustainability of learning and career development. This program demonstrated the importance of synergy between higher education institutions and vocational schools in bridging the competency gap and addressing the evolving needs of the modern logistics industry.